PRODUCTION FUNCTION AND INTERCONNECTION OF PRODUCTION FACTORS - N. Y. Kazhuro (Наука и техника)
The paper considers an interconnection between used factors, production process and product output under conditions of market economy. The possibilities concerning replacement of one production factor by the other one are analyzed in the paper. The paper determines justification limits of such  replacement and emphasizes a fundamental importance of a number of aspects that are to be taken into consideration while inter-replacing production factors.